The Innovation Process Of The Merdeka Curriculum In Learning At The Madrasah Ibtidaiyah - Miftahur Rohman; Wakib Kurniawan (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The implementation of Merdeka Curriculum in Madrasah Ibtidaiyah Bustanul ‘Ulum Jayasakti Anak Tuha is a challenge in facing the increasingly diverse and complex educational needs in the current era. This curriculum offers greater flexibility in developing learning materials that are relevant to the local context and religious values. This study aims to explore and analyse the implementation process of Merdeka Curriculum in Madrasah Ibtidaiyah Bustanul ‘Ulum Jayasakti Anak Tuha, as well as to understand its impact on the quality of learning and the development of student competencies. A qualitative approach with a case study as the main design was used in this study. Data were collected through in-depth interviews with teachers, participatory observation, and document analysis related to curriculum implementation. The results showed that the implementation of Merdeka Curriculum at Madrasah Ibtidaiyah Bustanul ‘Ulum Jayasakti Anak Tuha has successfully increased flexibility in curriculum development and enriched students’ learning experiences. However, challenges faced include the readiness of human resources in adopting this new curriculum and the need for ongoing support from the school and government to maintain consistency in its implementation.